Uterine tumors with neuroectodermal differentiation. A report of 4 cases - Dundr, Pavel; Fischerová, Daniela; Povýšil, Ctibor; Berková, Adéla; Bauerová, Lenka; Cibula, David (Pathology oncology research, 2010)
We report four cases of uterine tumors with neuroectodermal differentiation. One tumor had neuroectodermal component only; in the three other tumors, the neuroectodermal component was admixed with another component, namely rhabdomyosarcoma (1 case), and endometrioid adenocarcinoma (2 cases). Histologically, the neuroectodermal component consisted of small to medium sized cells arranged in diffuse sheets. The tumor cells had round nuclei with stippled to coarsely granular chromatin, mostly with non-prominent nucleoli, and scant eosinophilic or amphophilic cytoplasm. Immunohistochemically, 4/4 tumors showed expression of vimentin, synaptophysin and CD56; 3/4 tumors were CD99 and NSE positive; 2/4 tumors showed focal expression of S-100 protein; and 1/4 tumors had focal dot-like cytoplasmic positivity for cytokeratin AE1/AE3. FLI-1 was negative in all cases. FISH examination was performed and none of the tumors showed rearrangement of EWSR1 gene. Uterine tumors with neuroectodermal differentiation are rare; to the best of our knowledge only 44 cases have been reported in the literature to date, referred to as Ewing sarcoma, peripheral PNET (pPNET), PNET (not otherwise specified) and uterine tumors with neuroendocrine differentiation.
Keywords: proteiny vázající kalmodulin; senioři; Calmodulin-Binding Proteins; Aged; neuroektodermové nádory; Immunohistochemistry; lidé; lidé středního věku; Humans; RNA-Binding Protein EWS; Middle Aged; proteiny vázající RNA; Cell Differentiation; senioři nad 80 let; nádory dělohy; Aged, 80 and over; protein EWS vázající RNA; Gene Rearrangement; buněčná diferenciace; genová přestavba; imunohistochemie; ženské pohlaví; Female; Uterine Neoplasms; Neuroectodermal Tumors; RNA-Binding Proteins